1984
DOI: 10.1139/m84-074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of free-living nematodes and compost moisture on growth and yield in Agaricus brunnescens

Abstract: The responses of four mushroom cultivars ('PSU-310,' 'PSU-324,' 'PSU-348,' and 'PSU-344') exposed to free-living nematode infestations were compared in two experiments by quantitatively determining the amount of mycelium in compost samples using a laccase assay technique. The amount of mycelial production for cultivars 'PSU-310,' 'PSU-324,' and 'PSU-348' in the control treatments of both studies was similar. While cultivar 'PSU-344' produced less mycelium as shown by laccase production, mycelial production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It also reduces mushroom quality by causing sporophore distortion and/or by its physical presence on sporophores. Similar or even greater numbers of rhabditid nematodes/g of compost or casing material have been reported from many mushroom farms all over the world (Ingratta & Olthof, 1978;Hesling, 1979;McLeod & Nair, 1981 ;Sanderson et al, 1981 ;Kaufman et al, 1984) and it is a matter of speculation as to the extent of annual crop losses incurred by commercial growers.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It also reduces mushroom quality by causing sporophore distortion and/or by its physical presence on sporophores. Similar or even greater numbers of rhabditid nematodes/g of compost or casing material have been reported from many mushroom farms all over the world (Ingratta & Olthof, 1978;Hesling, 1979;McLeod & Nair, 1981 ;Sanderson et al, 1981 ;Kaufman et al, 1984) and it is a matter of speculation as to the extent of annual crop losses incurred by commercial growers.…”
Section: Discussionmentioning
confidence: 54%
“…However, nematode populations started to decline two weeks after inoculation, indicating that they should perhaps best be described as 'opportunistic substrate modifiers'. This view is substantiated by Kaufman et al (1984) who showed that extracts of a nematode-infected compost affected the growth of mushroom mycelium. Normally, mushrooms appear in distinct flushes at intervals of about 7 -14 days (Flegg & Wood, 1985).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Saprophagous rhabditid nematodes are commonly found in both compost and casing material (moss-peat/chalk) used for the cultivation of the mushroom Agaricus bisporus (Lange) Imbach (Hesling, 1979). High nematode populations are often associated with reductions in mycelial growth (Hesling, 1966; Kaufman, Lukezic &Bloom, 1984) and losses in yield (Ross & Burden, 1981; Sanderson, Marshall, Ovenden & Stengs, 1981), though a direct causal relationship has not been established. The effects of saprophagous nematodes on A .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of saprophagous nematodes on A . bisporus depend upon compost moisture (Kaufman et al, 1984) and on the type of mushroom strain cultivated (Klingler & Tschierpe, 1980; Ross & Burden, 1981). Direct pathogenicity by the nematodes is unlikely, as their stoma (buccal cavity) is structurally incapable of causing any significant physical damage to mushroom mycelium.…”
Section: Introductionmentioning
confidence: 99%